2007
DOI: 10.1038/nn2028
|View full text |Cite
|
Sign up to set email alerts
|

A versatile prion replication assay in organotypic brain slices

Abstract: Methods enabling prion replication ex vivo are important for advancing prion studies. However, few such technologies exist, and many prion strains are not amenable to them. Here we describe a prion organotypic slice culture assay (POSCA) that allows prion amplification and titration ex vivo under conditions that closely resemble intracerebral infection. Thirty-five days after contact with prions, mouse cerebellar slices had amplified the abnormal isoform of prion protein, PrP(Sc), >10(5)-fold. This is quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 32 publications
10
140
1
1
Order By: Relevance
“…The absence of effect of TREM2 on Aβ plaques and prion load is surprising; it suggests that the microglial activation state may not necessarily correlate with their phagocytic capacity. Together with our previous findings that depletion of microglia enhances prion replication in organotypic cerebellar slices (Falsig, et al, 2008), we hypothesize that the availability of microglia, and perhaps a basal level of activation, may be crucial for phagocytosis, whereas further activation does not appear to augment the clearance of prions. Accordingly, lipopolysaccharide-stimulated microglial activation did not enhance further phagocytosis of prions (Hughes, et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The absence of effect of TREM2 on Aβ plaques and prion load is surprising; it suggests that the microglial activation state may not necessarily correlate with their phagocytic capacity. Together with our previous findings that depletion of microglia enhances prion replication in organotypic cerebellar slices (Falsig, et al, 2008), we hypothesize that the availability of microglia, and perhaps a basal level of activation, may be crucial for phagocytosis, whereas further activation does not appear to augment the clearance of prions. Accordingly, lipopolysaccharide-stimulated microglial activation did not enhance further phagocytosis of prions (Hughes, et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, PrP Sc deposition and astrogliosis were similar in all three groups. Since the phagocytic activity of microglia is a well-established limiting factor for prion propagation within the brain (Falsig, et al, 2008,Kranich, et al, 2010, the unchanged PrP Sc deposition and prion infectivity titer suggested that the phagocytosis of prions by TREM2 -/-microglia was not markedly affected. However, TREM2 seems to be involved in microglial activation, as the prion-induced enhancement of IBA-1 reactivity was attenuated in TREM2 -/-mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For microglia depletion experiments, tga20 TK+ slices were treated with ganciclovir (GCV, 5 μg ml -1 ) for 14 days prior to antibody treatment. At this time point less than 1% of microglia were left in the tissue 39 . …”
Section: Manganese-enhanced Magnetic Resonance Imaging (Memri)mentioning
confidence: 90%